PENGETAHUAN ORANG TUA TENTANG KARIES GIGI ANAK SEKOLAH DI SD 1 KUTUH KUTA SELATAN - Apricillia,. P.M; Dewi, N.L.M.A; Artawan, I.K (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2021)
Background: Dental caries is a condition where the teeth’s enamel, dentin and cement tissues are damaged. In result, the hard tissue of teeth soften progressively and causing cavities. Parents are very influential in forming the children’s behavior. Moreover, parents’ knowledge underlies and supports the habit of cleaning their teeth and mouth. Parents are very influential in forming the children’s behavior. Moreover, parents’ knowledge underlies and supports the habit of cleaning their teeth and mouth. Method this research was a descriptive research which used analysis method. The research took place in SD 1 Kutuh Kuta Selatan. The samples’ number were 160 parents. The sampling techniques used in this research are non-probability sampling with consecutive sampling. Result The research’s result from 160 respondents about the level of parents’ knowledge about dental caries among elementary students shows that 138 (86,25%) respondents have good knowledge, 22 (13,75%) respondents have average knowledge, and there was no respondent who had lack of knowledge of the issue. This study aims to determine the level of parents’ knowledge about dental caries in elementary children at SD 1 Kutuh, Kuta Selatan in 2021. Conclusion The research can be concluded that the level of parents’ knowledge about dental caries among elementary students in SD 1 Kutuh Kuta Selatan is in good category